Factors influencing female intention to participate in science technology engineering mathematics (STEM) education in Pakistan - Sadia, Sajid (2022)
Despite global awareness on the issue of gender disparity in STEM education, the situation in developing countries, such as Pakistan, has not improved significantly. The research on female participation in STEM education in Pakistan context is still limited. Hence, to address this problem and fill the research gap, the present research work aims to identify the factors effecting female participation in STEM education in Pakistan. Based on Social Cognitive Career Theory (SCCT) and Theory of Planned Behavior (TPB), the present research proposes a framework of factors effecting female participation in STEM education in Pakistan. The proposed framework encompasses individual (i.e., self-concept, self-efficacy, attitude, career outcome expectancy and behavioral intention) as well as the contextual factors (parental involvement and income level). The quantitative research design is employed for this study and the data collection is done using the survey method. The data was gathered from 202 female students studying at the secondary level of education in five cities of Pakistan. The data was analyzed by using SPSS v. 23. In total, 10 hypotheses were proposed by the present research whereby the results have supported 7 hypotheses. The results indicated that self-concept and attitude positively, whereas parental involvement, when taken as an independent variable, negatively predicted female STEM self-efficacy. Furthermore, career outcome expectancy did not significantly predict female STEM self-efficacy however, it significantly and negatively predicted the female STEM intention. Moreover, the results have also illustrated that self-efficacy is a strong and positive predictor of female intention to pursue STEM education. In addition, the results for the moderating impact of parental income and parental involvement showed that parental involvement has a negative impact on the relationship between female STEM self-efficacy and intend to continue STEM education. As for the moderating impact of parental income, the results indicate that parental income moderates the relationship between STEM self-efficacy and intention in a way that with the increase in parental income, the self-efficacy decreases. However, after the parental income reaches a certain level, the efficacy starts increasing. The present study has not only contributed towards the body of knowledge by analyzing the relationship of the individual and contextual factors with the female intention to participate in STEM education, it has also provided a guideline for the government and non-governmental bodies in Pakistan to make suitable strategies in order to promote STEM education in females by reducing the impact of barriers.